Gallium nitride sintered body and method for producing same

By using gallium nitride powder with controlled oxygen and dopants, processed through a hot press mold, the method addresses instability and cost issues in gallium nitride film production, achieving high-strength, low-oxygen sintered bodies suitable for large-scale sputtering targets with n-type or p-type conductivity.

JP7600519B2Active Publication Date: 2024-12-17TOSOH CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2019182824
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-10-10
Filing Date
2019-10-03
Publication Date
2024-12-17
Estimated Expiration
2039-10-03

AI Technical Summary

Technical Problem

Existing methods for producing gallium nitride thin films face challenges such as instability due to metallic gallium melting during sputtering, high costs and complexity, poor homogeneity, and difficulty in achieving n-type or p-type conductivity, along with issues related to oxygen content and target size limitations.

Method used

A method involving the use of gallium nitride powder with controlled oxygen content and specific dopants, processed through a hot press mold with precise thermal expansion coefficients, to produce a large, high-density sintered body suitable for sputtering targets, which can be n-type or p-type semiconductors.

Benefits of technology

The method results in a gallium nitride-based sintered body with low oxygen content, high strength, and improved crystallinity, enabling stable film formation and cost-effective, large-scale production of sputtering targets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600519000001
    Figure 0007600519000001
  • Figure 0007600519000002
    Figure 0007600519000002
  • Figure 0007600519000003
    Figure 0007600519000003
Patent Text Reader

Abstract

To provide a manufacturing method of a sputtering target for n-type, p-type gallium nitride thin films having low oxygen content and high strength.SOLUTION: The invention provides a gallium nitride-based sintered body having a content of one or more kinds of dopants selected from a group consisting of Si, Ge, Sn, Pb, Be, Mg, Ca, Sr, Ba, Zn, Cd of 1 wt. ppm or over and 100000 wt. ppm or under and an oxygen content of 1 atm.% or under, and a manufacturing method thereof.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Gallium nitride has attracted attention as a raw material for the light-emitting layer of blue light-emitting diodes (LEDs) and blue laser diodes (LDs), and in recent years has been used in various applications such as white LEDs and blue LDs in the form of thin films or substrates, and is also attracting attention as a material for power devices and other applications in the future. Currently, gallium nitride thin films are generally manufactured by the metalorganic chemical vapor deposition (MOCVD) method. The MOCVD method is a method in which the vapor of the raw material is contained in a carrier gas and transported to the substrate surface, where the raw material is decomposed by reaction with the heated substrate, thereby growing crystals.

[0002] Another method for producing thin films other than MOCVD is the sputtering method, which physically bombards a target placed at the cathode with positive ions such as Ar ions, releasing the material that makes up the target with the collision energy, and depositing a film with approximately the same composition as the target material on a substrate placed opposite it. There are two types of sputtering: direct current sputtering (DC sputtering) and radio frequency sputtering (RF sputtering).

[0003] Until now, a metal gallium target has been used as a method for forming a gallium nitride thin film by sputtering (see, for example, Patent Document 1). However, when using a metal gallium target, since the melting point of metal gallium is about 29.8°C, it melts during sputtering, making it difficult to obtain a gallium nitride film with highly stabilized properties such as crystallinity and transparency. To prevent this, a method has been proposed in which an expensive cooling device is installed and the film is formed at a low power, but this method has the problem of reducing productivity and easily increasing the intake of oxygen into the film.

[0004] In addition, a high-density gallium nitride sintered body has also been proposed (see, for example, Patent Document 2), but according to the examples, it becomes dense under very high pressure conditions of 58 Kbar (5.8 GPa), and the equipment for applying such pressure is very expensive, so it is not possible to produce a large sintered body. Therefore, the sputtering target itself used in the sputtering method is very expensive, and it is difficult to make it large, so there is a problem that the film tends to be poor in homogeneity.

[0005] As a method for reducing the amount of oxygen contained, a method has been proposed in which the amount of oxygen is reduced by subjecting an oxygen-containing gallium nitride sintered body to a nitriding treatment (see, for example, Patent Document 3). However, there is a problem in that reducing the amount of oxygen beyond a certain level can cause cracks in the sintered body.

[0006] In addition, when using a direct current sputtering method, the resistivity of the sputtering target is required to be low. As a method for this purpose, a method has been proposed in which the resistivity of the sputtering target is reduced by infiltrating metallic gallium into the gallium nitride molded product (see, for example, Patent Document 4). However, this method reduces the resistance, but there is a problem that metallic gallium precipitates during bonding or sputtering, reacting with a solder material such as indium, causing the gallium nitride molded product to peel off, and discharging cannot be performed stably. As a countermeasure, a method has been proposed in which the precipitation of metallic gallium is suppressed by lining with a thin film of tungsten (see, for example, Patent Document 5), but there are problems such as an increase in the number of target preparation steps, which makes it complicated, and the need to use a special material, such as expensive tungsten material.

[0007] In addition, to construct devices, it is necessary to make gallium nitride into n-type and p-type, but until now there has been no sputtering target suitable for this purpose. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 11-172424 [Patent Document 2] JP 2005-508822 A [Patent Document 3] JP 2012-144424 A [Patent Document 4] JP 2014-159368 A [Patent Document 5] JP 2014-91851 A Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide a large, dopant-containing gallium nitride-based sintered body with a low oxygen content for obtaining a highly crystalline gallium nitride thin film that has been made into an n-type or p-type semiconductor by the addition of a dopant, and a method for producing the same. [Means for solving the problem]

[0010] In view of this background, the present inventors have conducted extensive research and have found that it is possible to produce a large-sized, high-density gallium nitride sintered body with a low oxygen content by adding various dopant sources to gallium nitride powder with a low oxygen content and performing processing using a hot press mold with an appropriate holding time and thermal expansion coefficient suited to gallium nitride sintering, thereby completing the present invention.

[0011] That is, the aspects of the present invention are as follows. (1) A gallium nitride sintered body having a content of one or more dopants selected from the group consisting of Si, Ge, Sn, Pb, Be, Mg, Ca, Sr, Ba, Zn, and Cd of 1 wtppm or more and 100,000 wtppm or less, and an oxygen content of 1 atm% or less. (2) The gallium nitride sintered body according to (1), wherein the dopant is one or more selected from the group consisting of Si, Ge, Sn and Pb. (3) The gallium nitride sintered body according to (1), wherein the dopant is one or more selected from the group consisting of Be, Mg, Ca, Sr, Ba, Zn, and Cd. (4) A gallium nitride sintered body according to any one of (1) to (3), characterized in that the flexural strength is 50 MPa or more. (5) The gallium nitride sintered body according to any one of (1) to (4), characterized in that the oxygen content is less than 0.3 atm %. (6) Density is 3.0 g / cm 3 More than 5.4g / cm 3 The gallium nitride sintered body according to any one of (1) to (5) above, characterized in that: (7) A gallium nitride sintered body according to any one of (1) to (6), characterized in that the average grain size of the sintered body is 1 μm or more and 150 μm or less. (8) A method for producing a gallium nitride-based sintered body by a hot pressing method according to any one of (1) to (7), characterized in that a gallium nitride powder containing an oxygen content of 1 atm% or less and a dopant source are used as raw materials, and the difference between the linear thermal expansion coefficient in a direction perpendicular to the pressing direction of the hot pressing mold and the linear expansion coefficient of the raw material is within 15%. (9) A method for producing a gallium nitride sintered body according to (8), characterized in that the hot press mold for obtaining a disk has a sleeve divided into three or more parts. (10) A sputtering target comprising the gallium nitride sintered body according to any one of (1) to (7). (11) A sputtering target according to (10), characterized in that no layer containing tungsten exists between the target member and the bonding layer. (12) A method for producing a gallium nitride thin film, comprising using the sputtering target according to (10) or (11).

[0012] The gallium nitride sintered body of the present invention is characterized in that the content of one or more dopants selected from the group consisting of Si, Ge, Sn, Pb, Be, Mg, Ca, Sr, Ba, Zn, and Cd is 1 wtppm or more and 100,000 wtppm or less, and preferably 3 wtppm or more and 50,000 wtppm or less. By obtaining a sintered body containing such a dopant, it is possible to make the formed gallium nitride thin film a p-type or n-type semiconductor. In addition, in order to make the gallium nitride sintered body of the present invention an n-type semiconductor, the dopant is preferably one or more selected from the group consisting of Si, Ge, Sn, and Pb, and particularly preferably Si, and in order to make the gallium nitride sintered body of the present invention a p-type semiconductor, the dopant is preferably one or more selected from the group consisting of Be, Mg, Ca, Sr, Ba, Zn, and Cd, and particularly preferably Mg and / or Zn.

[0013] The oxygen content is also characterized by being 1 atm% or less, preferably 0.5 atm% or less, more preferably less than 0.3 atm%, even more preferably 0.2 atm% or less, and even more preferably 0.1 atm% or less. By reducing the oxygen content in the gallium nitride sintered body, when it is used as a sputtering target, it is possible to reduce the inclusion of oxygen as an impurity during film formation and obtain a film with higher crystallinity.

[0014] Here, atm% is synonymous with at%, and is expressed as the ratio of the number of atoms of a specific element to the number of atoms of all elements contained. For example, in gallium nitride containing oxygen, when gallium, nitrogen, and oxygen are each contained in wt%, the oxygen content (atm%) is Oxygen content (atm%) = (Oxygen content (wt%) / Oxygen atomic weight) / ((Gallium content (wt%) / Gallium atomic weight) + (Nitrogen content (wt%) / Nitrogen atomic weight) + (Oxygen content (wt%) / Oxygen atomic weight)) It becomes.

[0015] The gallium nitride sintered body of the present invention preferably has a flexural strength of 40 MPa or more, more preferably 50 MPa or more, and particularly preferably 60 MPa or more.

[0016] The gallium nitride sintered body of the present invention has a density of 3.0 g / cm 3 More than 5.4g / cm 3 It is preferable that the concentration is 3.5 g / cm or less, and more preferably 3.5 g / cm 3 More than 5.4g / cm 3 Less than 4.0 g / cm 3 More than 5.4g / cm 3 The density of the gallium nitride sintered body mentioned here refers to the density including the open pores, and refers to the measurement result of the bulk density according to JIS R 1634. Such a gallium nitride sintered body can be used as a sputtering target.

[0017] The gallium nitride sintered body of the present invention preferably has an average particle size (D50) of 1 μm or more and 150 μm or less, more preferably 5 μm or more and 100 μm or less, and particularly preferably 9 μm or more and 80 μm or less. By setting the particle size to such an extent, it becomes possible to obtain a gallium nitride sintered body having a smaller amount of oxygen and high strength.

[0018] The gallium nitride sintered body of the present invention may contain Al, In, and the like other than the dopant.

[0019] Next, a method for producing a gallium nitride sintered body according to the present invention will be described.

[0020] The method for producing a gallium nitride sintered body of the present invention uses gallium nitride powder having an oxygen content of 1 atm% or less and a dopant source as raw materials, and is a method for producing a gallium nitride sintered body in which the difference between the linear thermal expansion coefficient in the direction perpendicular to the pressing direction of a hot press mold and the linear expansion coefficient of the raw material is within 15%.

[0021] In order to obtain a low-oxygen gallium nitride sintered body without generating cracks in the sintered body, it is necessary to sinter the gallium nitride sintered body without applying stress to it. That is, the manufacturing method of the present invention is a manufacturing method of a gallium nitride sintered body by hot pressing, and is characterized in that gallium nitride powder with an oxygen content of 1 atm% or less and a dopant source are used as raw materials, and the difference between the linear thermal expansion coefficient in the direction perpendicular to the pressure direction of the hot press mold and the linear expansion coefficient of the raw material is within 15%. With this manufacturing method, it is possible to manufacture even a gallium nitride sintered body containing a dopant.

[0022] The method for producing a gallium nitride sintered body will be described in further detail below.

[0023] First, the oxygen content of the gallium nitride powder used as the raw material must be 1 atm% or less. More preferably, it is less than 0.5 atm%, more preferably 0.3 atm% or less, more preferably 0.2 atm% or less, and even more preferably 0.1 atm% or less. In order to reduce oxygen, it is necessary to suppress oxidation of the surface, so it is preferable that the specific surface area of ​​the powder is small, and more preferably 0.01 m. 2 / g or more 1.5m 2 / g or less, more preferably 0.01m 2 / g or more 0.8m 2 The amount of oxygen mixed in from the powder can be reduced by using such a powder. 2 If the specific surface area is smaller than 1 / g or more, the crystal particles are too large, so the adhesive force between the particles is weak, making it difficult to maintain the shape during final firing. Furthermore, the sinterability generally decreases, making firing difficult.

[0024] In order to obtain a gallium nitride sintered body with sufficient strength as a sputtering target, the bulk density of the raw material gallium nitride powder must be 1.0 g / cm 3 More than 3.0g / cm 3 It is preferably less than 1.4 g / cm 3 More than 3.0g / cm 3The light bulk density is a value calculated by filling a container with powder without applying any load such as vibration, and dividing the volume of the powder by the volume of the container. 3 If the light bulk density is increased to the extent that the strength of the granules constituting the powder becomes too high, the granules remain uncrushed during molding and sintering, resulting in a significant decrease in the strength of the gallium nitride sintered body.

[0025] In addition, the average particle diameter (D50) of the gallium nitride used as the raw material is preferably 1 μm or more and 150 μm or less. It is more preferably 5 μm or more and 100 μm or less, and even more preferably 9 μm or more and 80 μm or less. By using such powder, it is possible to manufacture a gallium nitride sintered body that is both sinterable and low-oxygen. In particular, in the case of gallium nitride, the sintering start temperature and the decomposition temperature are close to each other, the sintering temperature range is narrow, and the grains do not grow significantly during sintering, so the distribution of the primary particles before sintering has a large effect on the gallium nitride sintered body. The particle diameter of the primary particles refers to the diameter of the smallest unit particle observed by SEM, and the average particle diameter refers to the value at 50% grain diameter after measuring at least 100 particles by the diameter method. The particles for which the average particle diameter is measured here are gallium nitride particles. In the case of molded products using powders within this range, the particle size is larger than conventional powders and the adhesive strength is weaker. Therefore, if there are open pores large enough to allow immersion, the bonding strength between the particles is relatively weak. Therefore, when Ga is immersed, cracks will occur due to the stress generated during immersion and the difference in thermal expansion coefficient caused by heating and sputtering.

[0026] In order to obtain high crystallinity in the sputtered film and because the semiconductor characteristics change when an element is added, it is desirable to use gallium nitride powder that contains as few impurities as possible as the raw material.

[0027] The dopant source is not particularly limited, but is preferably a nitride or an alloy with gallium, since it is preferable that oxygen is not mixed in and that other impurities are not contained. Examples of nitrides include silicon nitride, germanium nitride, tin nitride, beryllium nitride, magnesium nitride, gallium-magnesium alloy, calcium nitride, strontium nitride, zinc nitride, and cadmium nitride.

[0028] To make the gallium nitride sintered compact of the invention an n-type semiconductor, the dopant source is preferably one or more selected from the group consisting of silicon nitride, germanium nitride, and tin nitride, and silicon nitride is particularly preferred. To make the gallium nitride sintered compact of the invention a p-type semiconductor, the dopant source is preferably one or more selected from the group consisting of beryllium nitride, magnesium nitride, gallium-magnesium alloy, calcium nitride, strontium nitride, zinc nitride, and cadmium nitride, and magnesium nitride and / or zinc nitride are particularly preferred.

[0029] In order to achieve both low oxygen and high dispersibility, the particle size of the dopant source is preferably 1 / 10 to 10 times the average particle size of the gallium nitride powder. By setting the particle size in this range, it becomes possible to highly disperse the contained elements without increasing the oxygen.

[0030] The sintering method used is the hot press method, which sinters powder by applying pressure and heat, and uniaxial pressure is applied while heating to assist diffusion during sintering, making it possible to sinter materials that have a low diffusion coefficient and are difficult to sinter.

[0031] The difference in the linear thermal expansion coefficient in the direction perpendicular to the pressure direction of the hot press mold from the thermal expansion coefficient of the raw material to be put in is preferably within 15%, more preferably within 10%, and even more preferably within 5%. More preferably, it is +0.1% or less and -0.5% or more with respect to the thermal expansion coefficient of the raw material. In the case of gallium nitride, it is 5.0×10 -6 / K or more 7.0×10 -6 / K or less, and more preferably 5.0×10 -6 / K or more 6.0×10 -6 / K or less. By using materials with a thermal expansion coefficient in this range, the linear thermal expansion coefficient becomes close to that of gallium nitride, making it possible to reduce the stress applied when enlarging the size. In the case of small sizes, sintering was possible even if the linear thermal expansion coefficient was different because the dimensional difference was small, but fine cracks were included, which was a cause of reduced strength. 3 If the temperature exceeds this range, the difference in dimensions due to the difference in thermal expansion will become large, causing stress during firing and resulting in cracks. -6 / K or less, when pressure sintering is performed at a specified temperature, the shrinkage of the hot press mold is smaller than that of the gallium nitride sintered body when the temperature is decreased, resulting in large tensile stress and cracking of the gallium nitride sintered body. -6 3. At temperatures of 1000 to 2000 K or more, the hot press mold shrinks more than the gallium nitride sintered body when the temperature is lowered, generating external compressive stress, which in turn causes cracks in the gallium nitride sintered body, resulting in a decrease in strength and breakage.

[0032] The firing temperature is 1060° C. or higher and lower than 1200° C. A temperature of 1060° C. or higher is necessary to promote the sintering of gallium nitride, and a temperature of less than 1200° C. is required to suppress the decomposition of gallium nitride into nitrogen and metallic gallium to a certain amount. In addition, the pressure during firing is preferably 30 MPa or higher and 100 MPa or lower, and more preferably 40 MPa or higher and 90 MPa or lower, in order to improve the density of the gallium nitride-based sintered body.

[0033] The firing temperature depends on the particle size of the powder used; the larger the particle size, the higher the temperature that can be applied.

[0034] The retention time during sintering is preferably 2 hours or more and 5 hours or less. More preferably, it is 3 hours or more and 4 hours or less. If it is less than 2 hours, the adhesion between particles does not progress even if the density increases due to partial decomposition of gallium. If it is sintered for longer than 5 hours, the decomposition progresses and there are no fine particles, so that the strength cannot be maintained even if the density increases. By sintering within this range, it is possible to suppress decomposition while progressing sintering, and a gallium nitride sintered body with higher strength than ever before can be obtained.

[0035] The hot press is performed in a vacuum atmosphere. The degree of vacuum at the start of heating is 10 Pa or less, and 1×10 -1 Pa or less is preferable, and 5×10 -2 Pa is more preferable, 1×10 -2 It is particularly preferable that the pressure is equal to or less than Pa. This makes it possible to reduce oxygen and oxygen elements such as water that are mixed in from the atmosphere, and to suppress oxidation during firing.

[0036] In addition, when sintering in a vacuum, the decomposition of the gallium nitride powder gradually progresses from around 1060°C, but by sintering in a vacuum, some of the metallic gallium produced by the decomposition is discharged to the outside from the gallium nitride sintered body together with nitrogen, which is the decomposition gas. For this reason, it is preferable that the clearance between the die and the upper punch in the hot press mold is 0.2 mm or more. Alternatively, it is preferable to use a low-density material such as carbon felt between the powder and the upper and lower punches.

[0037] The hot press mold preferably includes a split sleeve 1. More preferably, the sleeve is split into three or more parts, and even more preferably, into four or more parts. The maximum number of parts is preferably six or less. Splitting the sleeve in this way makes it easier to remove the gallium nitride sintered body, and makes it possible to prevent cracking and chipping.

[0038] In order to reduce the amount of oxygen adsorbed to the mold, it is preferable to perform a pre-baking process before firing, which makes it possible to reduce the amount of moisture adsorbed to the hot press device and mold before firing.

[0039] When hot pressing is performed under the above conditions, metallic gallium does not become an inhibitor during sintering and is contained in an appropriate amount, so that sintering proceeds to obtain a gallium nitride sintered body with high density and suppressed oxidation. In particular, metallic gallium decomposes partially in the range of 1090°C to 1150°C, but sintering of gallium nitride also proceeds, so that pressure sintering is performed in a high vacuum to allow sintering of gallium nitride to proceed without being inhibited by metallic gallium, thereby improving density. When gallium nitride is used as a sputtering target, it is preferable that the gallium nitride sintered body has electrical conductivity, and for this purpose, metallic gallium is preferably present.

[0040] The obtained gallium nitride sintered body is preferably in a disk shape, since the disk shape allows thermal expansion and contraction to be uniform in the circumferential direction, making it possible to suppress the stress applied to the gallium nitride sintered body.

[0041] The obtained gallium nitride sintered body may be processed to a predetermined size depending on the application such as a sputtering target, etc. The processing method is not particularly limited, and a surface grinding method, a rotary grinding method, a cylindrical grinding method, etc. may be used.

[0042] The gallium nitride sintered body may be fixed (bonded) to a flat or cylindrical support with an adhesive such as a solder material as necessary to form a sputtering target. It is preferable that the sputtering target does not have a layer containing tungsten between the target member and the bonding layer. By not using an expensive metal tungsten target, costs can be reduced, and a tungsten film formation process is unnecessary, improving productivity.

[0043] In addition, in the sputtering target of the present invention, it is preferable to use a tin-based solder material, an indium-based solder material, or a zinc-based solder material as the bonding layer. Among these, indium solder is particularly preferable because it has high electrical conductivity and thermal conductivity, is soft, and is easily deformed.

[0044] In addition, in the sputtering target of the present invention, the support is preferably made of a metal such as Cu, SUS, or Ti because of its high thermal conductivity and strength. As for the shape of the support, it is preferable to use a flat support for a flat molded product, and a cylindrical support for a cylindrical molded product.

[0045] Next, a method for producing the sputtering target of the present invention will be described.

[0046] The sputtering target of the present invention is manufactured by bonding a gallium nitride sintered body to a support via a bonding layer. For the bonding layer, a tin-based solder material, an indium-based solder material, a zinc-based solder material, etc. can be used. When an indium-based solder material is used, a layer for improving wettability may be formed between the gallium nitride sintered body and the solder material in order to improve the indium wettability to the gallium nitride sintered body. The material of the layer is preferably inexpensive and has high wettability to indium, for example, a nickel-based or chromium-based material. This layer is preferably formed uniformly over the entire interface with the solder material. There is no particular limitation on the method for forming such a barrier layer, and sputtering, vapor deposition, coating, etc. can be used. Effect of the Invention

[0047] The gallium nitride sintered body of the present invention is large, has a low oxygen content, and has high strength, and is suitable for use as a sputtering target for practical production. EXAMPLES

[0048] The present invention will be described below with reference to examples, but is not limited thereto. (Dopant content measurement) The dopant content was measured by ICP-AES, and when it was below the lower limit of measurement by ICP-AES, it was measured by GDMS (glow discharge mass spectrometry). (Lightweight bulk density) The measurements were carried out using a powder tester PT-N type (manufactured by Hosokawa Micron). (Density of gallium nitride sintered body) The density of the gallium nitride sintered body was measured in accordance with the bulk density measurement method specified in JIS R1634. (oxygen content) The oxygen content was measured using an oxygen / nitrogen analyzer (manufactured by LECO). (Measurement of average particle size (D50)) The average particle size (D50) was measured by the diameter method in at least three fields of view from SEM observation images, and the 50% particle size was taken as the average particle size after measuring more than 100 particles. The measurement subjects were only gallium nitride particles in gallium nitride powder and gallium nitride sintered compacts. (flexural strength) The flexural strength of the sintered body was measured according to JIS R 1601 after machining to an appropriate size.

[0049] Example 1 Metallic silicon was added to 600g of gallium nitride powder shown in Table 1 to achieve a prescribed concentration, and after mixing uniformly, the mixture was placed in a 180mmφ carbon mold and then hot pressed. Firing was started with the degree of vacuum reached before the start of heating shown in Table 2, the temperature was raised at 200°C / h, and finally increased to the temperature shown in Table 2. The pressure conditions at this time were raised to the pressure shown in Table 2 when the maximum temperature was held, and hot pressing was performed with the temperature and pressure held for 2 hours. The temperature was finally lowered to approximately 50°C, the mold was removed, and the sintered body was recovered. In all cases, the temperature was lowered to 150cm 2 The density, oxygen content, average particle size (D50), and dopant content of the obtained gallium nitride sintered body are shown in Table 3.

[0050] The results of the impurity amounts in Example 1 are shown in Table 4.

[0051] (Examples 2 and 3) Silicon nitride was added to 100g of gallium nitride powder shown in Table 1 to a specified concentration, and after mixing uniformly, it was placed in a 78mmφ carbon mold and then hot pressed. Firing was started under the conditions of the ultimate vacuum before the start of the temperature rise shown in Table 2, the temperature was raised at 200°C / h, and finally increased to the temperature in Table 2, and the pressure conditions at that time were raised to the pressure in Table 2 when the maximum temperature was held, and the hot press treatment was performed with the temperature and pressure held for 2 hours. The temperature was finally lowered to about 50°C, the mold was removed, and the sintered body was collected. The density, oxygen content, average particle size (D50), and dopant content of the obtained gallium nitride sintered body are shown in Table 3.

[0052] (Examples 4 to 6) A gallium nitride sintered body was produced under the same conditions as in Example 2, except that the dopant source was changed to that in Table 1. Table 3 shows the density, oxygen content, average particle size (D50), and dopant content of the obtained gallium nitride sintered body.

[0053] The results of the impurity amounts in Example 4 are shown in Table 4.

[0054] Example 7 A gallium nitride sintered body was produced under the same conditions as in Example 2, except that the dopant source was changed to that in Table 1. Table 3 shows the density, oxygen content, average particle size (D50), and dopant content of the obtained gallium nitride sintered body.

[0055] (Comparative Examples 1 and 2) Gallium nitride was produced under the same conditions as in Example 2, except that the dopant source was changed to that in Table 1. The density, oxygen content, average particle size (D50), and dopant content of the obtained gallium nitride sintered body are shown in Table 3. Cracks occurred during sintering, and the desired sintered body was not obtained.

[0056] Comparative Example 3 Gallium nitride was produced under the same conditions as in Comparative Example 1, except that the dopant source was changed to that in Table 1. The density, oxygen content, average particle size (D50), and dopant content of the obtained gallium nitride sintered body are shown in Table 3. The oxygen content was high, and a sintered body of the quality required for use as a sputtering target could not be obtained.

[0057] [Table 1]

[0058] [Table 2]

[0059] [Table 3]

[0060] [Table 4]

Claims

1. A gallium nitride sintered body characterized in that the content of one or more dopants selected from the group consisting of Mg, Ca, Sr, Ba, Zn, and Cd is 1 wtppm or more and 100,000 wtppm or less, the oxygen content is 1 atm% or less, and the flexural strength is 50 MPa or more.

2. 2. The gallium nitride sintered body according to claim 1, characterized in that the oxygen content is less than 0.3 atm %.

3. A gallium nitride sintered body as described in claim 1 or 2, characterized in that the content of the dopant is 3 wtppm or more and 50,000 wtppm or less.

4. Density is 3.0 g / cm 3 5.4g / cm or more 3 4. The gallium nitride sintered body according to claim 1, wherein the gallium nitride sintered body is:

5. The gallium nitride sintered body according to claim 1, characterized in that the density is 3.5 g / cm 3 or more and 5.4 g / cm 3 or less.

6. 6. The gallium nitride sintered body according to claim 1, wherein the average grain size of the sintered body is from 1 μm to 150 μm.

7. 7. A method for producing a gallium nitride sintered body by hot pressing, comprising the steps of: using gallium nitride powder having an oxygen content of 1 atm % or less and a dopant source as raw materials; performing hot pressing in a vacuum atmosphere; and determining whether the difference between the linear thermal expansion coefficient in a direction perpendicular to the pressure direction of the hot press mold and the linear expansion coefficient of the raw material is within 15%.

8. 8. The method for producing a gallium nitride sintered body according to claim 7, characterized in that the hot press mold for producing a disk has a sleeve divided into three or more parts.

9. A sputtering target comprising the gallium nitride sintered body according to any one of claims 1 to 6.

10. 10. The sputtering target of claim 9, wherein there is no tungsten-containing layer between the target member and the bonding layer.

11. A method for producing a gallium nitride thin film, comprising using the sputtering target according to claim 9 or 10.

Citation Information

Patent Citations

  • Production of gallium compound

    JP1999172424A

  • Silicon nitride sintered compact and sputtering target made of the same

    JP2000313670A

  • Sintered polycrystalline gallium nitride and its production method

    JP2005508822A

  • Thin film of aluminum nitride and process for producing the thin film of aluminum nitride

    JP2009228131A

  • Gallium nitride sintered body or gallium nitride molded article, and method for producing them

    JP2012144424A